Emotions and entrepreneurship education: State of the art and future research agenda - Víctor Centeno Pérez; Juha Kansikas (Institut für Mittelstandsforschung (IfM) Bonn, 2019)
Entrepreneurship education holds the potential to mitigate unemployment and boost prosperity, yet emotions, one of its sources of strength, remain underutilized. There is a strong consensus that emotions are tightly linked to learning processes, and vice versa. Across entrepreneurship education, the role of emotions as learning drivers is acknowledged but barely exploited. Following a systematic and reflective approach, the primary goal of this article is to examine the state of the art of the empirical evidence that touches upon the subject of entrepreneurship education and emotions. From the analysis undertaken, three relevant findings arise: 1) the research within the field has placed emphasis more on the by-products of emotions, such as emotional competencies, affective forecasting, emotional events as relevant in the execution of action-based entrepreneurship education schemes, and less on the determination and underpinnings of specific emotions critical to learning in entrepreneurship education; 2) despite the learning potential of emotions, the pedagogical use of emotions in entrepreneurship education remains neglected; and 3) there is an exclusive focus on the emotions on the student side at the expense of entrepreneurship educators' emotions, which are tremendously relevant. In the same vein, the study proposes a future research strategy based on three pillars: 1) identification of the specific emotions linked to entrepreneurial learning from both the student and teacher viewpoint; 2) the need to explore unconventional paths to integrate the strengths of emotions and emotion regulation into the teaching and learning of entrepreneurship; and 3) the incorporation of new technologies and methodologies to measure and take advantage of emotions to ehnance entrepreneurial learning among existing entrepreneurship education programmes.
Additional information: In ihrem Beitrag geben Victor Pérez und Juha Kansikas nicht nur einen Überblick über die Ergebnisse der bisherigen Forschung zum Thema "Entrepreneurship Education und Emotionen", sondern diskutieren in diesem Zusammenhang auch weitere interessante Forschungsgebiete.
Keywords: L26; M13; O33; 330; entrepreneurship education; emotions and entrepreneurship; entrepreneuriallearning